2023
DOI: 10.1007/s12599-023-00799-7
|View full text |Cite
|
Sign up to set email alerts
|

Social Support as Technostress Inhibitor

Abstract: Due to ongoing digitalization and the social distancing measures that came along with the COVID-19 pandemic, the working conditions and environments have changed for many individuals. Because of increased telework, the use of digital technologies for communicating and collaborating at work has been intensified, which can cause technostress. With longitudinal data from two surveys – one before and one during the COVID-19 pandemic – the paper analyzes the relationship between four social support dimensions (supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A study by Tarafdar et al (2014) found that employees who perceived higher levels of supervisor support reported lower levels of technostress. Similarly, a study by Lanzl (2023) found that social support from supervisors was negatively related to technostress. Therefore, supervisor support can have a significant impact on reducing technostress among FLEs.…”
Section: Conceptual Development 31 Organizational Resources 311 Socia...mentioning
confidence: 87%
See 3 more Smart Citations
“…A study by Tarafdar et al (2014) found that employees who perceived higher levels of supervisor support reported lower levels of technostress. Similarly, a study by Lanzl (2023) found that social support from supervisors was negatively related to technostress. Therefore, supervisor support can have a significant impact on reducing technostress among FLEs.…”
Section: Conceptual Development 31 Organizational Resources 311 Socia...mentioning
confidence: 87%
“…Social support can be an effective inhibitor of technostress creators. Social support can reduce technostress creators' negative impact by providing employees with a sense of security and assistance when problems with digital technologies occur (Lanzl, 2023). This study concentrated on workplace social support (i.e., organizational, supervisor, and co-worker).…”
Section: Conceptual Development 31 Organizational Resources 311 Socia...mentioning
confidence: 99%
See 2 more Smart Citations